1988
DOI: 10.1038/bjc.1988.224
|View full text |Cite
|
Sign up to set email alerts
|

Survival of breast cancer patients diagnosed during pregnancy or lactation

Abstract: Summary This survival study includes 20 breast cancer patients diagnosed during pregnancy and 15 patients diagnosed during the lactation period. The survival rate of these patients is compared with that of ordinary breast cancer patients taking stage of the disease, age and calendar-year at diagnosis into account. The pregnancy group showed a significantly. poorer prognosis compared with the control groups. Only 3 out of 20 survived more than 4 years. The tendency of a worse prognosis for the lactation group t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 7 publications
2
44
0
2
Order By: Relevance
“…Their results showed no difference in survival for pregnant patients compared with matched controls of the same age, whereas when those under 40 were compared with patients over 40 years old, there was a significant decrease in 5-year survival in the younger group. Other studies have not used age-matched controls, though Tretli et al (1988) in a study of 20 breast cancer patients diagnosed during pregnancy found a significantly poorer prognosis for these women after taking stage of disease, age and calendar year at diagnosis into account.…”
Section: Pregnancy or Lactation At Breast Cancer Diagnosismentioning
confidence: 99%
“…Their results showed no difference in survival for pregnant patients compared with matched controls of the same age, whereas when those under 40 were compared with patients over 40 years old, there was a significant decrease in 5-year survival in the younger group. Other studies have not used age-matched controls, though Tretli et al (1988) in a study of 20 breast cancer patients diagnosed during pregnancy found a significantly poorer prognosis for these women after taking stage of disease, age and calendar year at diagnosis into account.…”
Section: Pregnancy or Lactation At Breast Cancer Diagnosismentioning
confidence: 99%
“…Several studies have found evidence of a diagnostic delays in pregnant women (2-7), which may explain why results from some, but not all, studies show that women with PABC have larger tumors and are more likely to have positive nodes, metastases and vascular invasion compared with nonpregnant women with breast cancer (2,5,(8)(9)(10). A poor prognosis in PABC (4,(8)(9)(10)(11)(12)(13)(14) has previously primarily been attributed to diagnostic delays (7,15). However, few studies have investigated whether the prognosis varies by time of diagnosis (during pregnancy and different postpartum time intervals).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have investigated whether the prognosis varies by time of diagnosis (during pregnancy and different postpartum time intervals). Some studies have distinguished between pregnant and lactating women (2,4,5,10,14), while most investigators have focused on cancers diagnosed after childbirth in 1-year intervals following delivery (8,9,12,13). In all these studies, ranging in size from 35 to 708 cases of PABC, proximity to pregnancy was associated with a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ives et al found an average of one month (1-104 weeks) from symptom to diagnosis in pregnant breast cancer cases and Ibrahim et al found symptom to diagnosis time to be shorter in pregnant breast cancer cases than the nonpregnant cases (5.6 months versus 9.4 months respectively) (40,41). The summary of studies on this issue is presented in Table 1 (13,16,(39)(40)(41)(42)(43)(44). For early diagnosis of PABC, all pregnant women should have a breast examination during the first antenatal visit.…”
Section: The Diagnosis Of Pregnancy Associated Breast Cancer (Pabc)mentioning
confidence: 91%